SUSTAINABLE HOTEL STRATEGY EXECUTION: A REVIEW AND WAY FORWARD - Migale, Harvey; Stimie, Johann; Brent, Alan (The South African Journal of Industrial Engineering, 2019)
Tourism, the third largest industry in the world, is worth US 1.4 trillion, and represents 10 per cent of the world’s GDP. Tourism is also responsible for five per cent of the world’s carbon dioxide emissions, of which hotels and other types of accommodation account for one per cent. In this context, a sustainable hotel strategy execution is essential for maintaining and improving our planet’s socio-economic and ecological balance. This systematic review lays the foundation for the development of a sustainable hotel strategy decision and execution support tool. Systems thinking and system dynamics allow the modelling of the interdependent elements of a complex hotel system, followed by a scenario simulation for proper strategy–analysis and strategy-decision. The execution of the chosen strategy can then be compared with the expected results. With a view to appraising the potential development of such a sustainable hotel strategy execution model for any tourism destination, a systematic literature review was carried out on existing sustainable strategy execution models and tools, as well as the existing use of systems thinking and system dynamics in the tourism and hotel sector.